Evaluation of surgically assisted rapid maxillary expansion with and without midpalatal split - Sant'Ana, L. F. M.; Pinzan-Vercelino, C. R. M.; Gurgel, J. A. [UNESP]; Carvalho, P. S. P. (Churchill Livingstone, 2016)
The purpose of this study was to compare the efficacy and the patients' subjective symptomatology between surgically assisted rapid maxillary expansion (SARME) with midpalatal split and SARME without midpalatal split. The sample consisted of 24 consecutive adult patients requiring treatment with SARME, who were divided into two groups. Group 1 patients (n = 14) underwent SARME with midpalatal split, and group 2 patients (n = 10) underwent SARME without midpalatal separation. The efficacy of the technique was assessed in relation to the presence of a diastema between the upper incisors and radiographic evidence of separation of the maxillary bones in the midpalatal suture. The patients' symptomatology was evaluated using pain scores. The results demonstrated a greater efficacy for group 1 (P = 0.00). The discomfort of surgery assessed immediately postoperative and at 14 days postoperative was similar in the two groups. Both surgical techniques were tolerated by the patients; the midpalatal separation did not influence patient discomfort due to surgery. The two groups showed a statistically significant difference regarding discomfort during appliance activation and pain during the postoperative phase, with group 2 showing greater discomfort.
Keywords: surgically assisted rapid maxillary expansion; surgical procedures; operative; efficacy